THE MAPPING AND NEED ANALYSIS OF ENGLISH COMPETENCIES FOR TOURIST GUIDES IN MALANG - Noverita Wahyuningsih; Novitasari; Maya Rizki Fauzia; Ririn Pratiwi Suharto (Esteem Journal of English Education Study Programme, 2024)
A professional tour guide should possess good competence in English to communicate with their guests. However, the truth often reveals that many tour guides have inadequate English skills and they are not confident enough to offer tours. They need a kind of training or an education program to increase their knowledge and skills in tourists guiding. This is a regular occurrence in underdeveloped nations, such as Indonesia. Consequently, they need specific tourist guiding knowledge and skills as well as English mastery. This study aims to identify demographic data of tourist guides in Malang, both their strengths and weaknesses in English competence and also to map and analyze the need for English competence for tourist guides in the city of Malang. The object of this research is 22 tourist guides of Malang city. This research was conducted in Malang city. This study uses mixed method where the researcher uses both quantitative and qualitative approach in order to produce a better understanding of the problem. Researchers used 2 types of data collection tools, namely questionnaires and interview guidelines. The questionnaire used in the form of a closed question questionnaire with a Likert scale along with open questions. FGDs were also conducted to obtain in-depth information about research problems. The findings revealed that tour guides required four different types of English skills. The learning activities required are conversations, discussions and brainstorming, as well as individual presentations or learning activities that emphasize speaking skills. There are some suggestions proposed to curriculum developers, Department of tourism and Indonesian tour guides. Considering the significance of needs analysis, prior to developing training program, it is pivotal to conduct needs analysis to probe information on language proficiency, learning objectives and learning preference of the learners.